Uji Antipiretik Patch Ekstrak Etanol Bawang Merah (Allium ascalonicum L.) dengan Matriks Chitosan dan Enhancer Tween-80 - Willyanto, Jennifer Rachel; Hamid, Iwan Sahrial; Widodo, Teguh (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2018)
Onion is a traditional medicine that has a lot of pharmacological potential. Flavanoid compounds found in onions have an antipyretic effect that acts as an inhibitor of cyclooxygenase (COX) enzymes that play a role in the formation of prostaglandins. In this study red onion is formulated into a patch because of its practical use and can avoid the first metabolic pathway. This study aims to analyze the effect of onion ethanol extract patch (Allium ascalonicum L.) on the decrease of body temperature and the number of monocytes in white rats induced by DPT vaccine. This study used 4 treatment groups: positive controls administered paracetamol syrup, negative controls given placebo patch, treatment group 1 treated with red onion ethanol extract without enhancers and treatment group 2 treated with an red onion ethanol extract with enhancers. Rats adapted for 7 days before temperature being measured and the blood being collected from the rat tail in order to calculate the number of monocytes. The animal temperature was measured after injected with vaccine DPT at 15, 30, 45, 60, 75, 90, 105, 120, 150, 180 minutes meanwhile number of monocyte were calculated every 15 minutes for 120 minutes. The results showed that there was no significant difference in monocyte count of treatment group with positive control but there were significant differences in temperature. The use of onion ethanol extract patch may decrease the temperature and number of monocytes in white mice induced by DPT vaccine.